Legitimacy and accountability in the global governance of large-scale agricultural land investments. (2nd January 2016) - Johnson, Hope
ABSTRACT: This article examines the international regulatory framework for large-scale agricultural land investments ('LSALIs'). Population growth, natural resource scarcity, and the financial and food price crises have made financial actors revise their long-held hesitation towards direct investment in farmland. Although these investments could inject much-needed capital into rural areas, LSALIs have been connected with grievous human rights violations and environmental degradation. This article finds that the instruments designed to promote socially and environmentally responsible LSALIs have increasing levels of legitimacy but lack accountability mechanisms. As a result, the emerging regulatory framework for LSALIs does not create the balance required between protecting investors from host state interference and ensuring socially and environmentally responsible agricultural investments.